The Relationship Between Learning Motivation, Portfolio Based Assessment, and Students’ Writing Ability - Lungguh Halira Vonti (Pedagogia: Jurnal Ilmiah Pendidikan, 2016)
The study is aimed to reveal the relationship between learning motivation, portfolio based assessment with the students’ writing ability. The study was conducted in second semester of English Education Study Program in Faculty of Teachers Training and Educational Sciences, Pakuan University. The population of the study is the second semester of the English Department, Faculty of Teachers Training and Educational Sciences, Pakuan University. From the population, the sample of the study is two classes with 56 students. The method of the study is correlative study with the technique of data analysis multiple regression. The instruments used by the researcher are motivation questionnaire, portfolio project, questionnaire on students’ perception toward portfolio based assessment, and writing test. From the study, it can be concluded that the students’ learning motivation has significant positive relationship with the students’ writing ability. The second result is the positive relationship between portfolio based assessment and the students’ writing ability. From the data analysis, it is found out that the students who got high score in their portfolio project, obtained high score in writing test.